A Comparative Tissue‐specific Metabolite Analysis and Determination of Protodioscin Content in Asparagus Species used in Traditional Chinese Medicine and Ayurveda by use of Laser Microdissection, UHPLC–QTOF/MS and LC–MS/MS. Issue 6 (16th April 2014) - Jaiswal, Yogini; Liang, Zhitao; Ho, Alan; Chen, Hubiao; Zhao, Zhongzhen
ABSTRACT Introduction Asparagus is esteemed in Traditional Chinese Medicine and Ayurveda, and it is commercially one of the most important drugs in the global herbal market. Comparative metabolite profiling of different species would help in determining the similarities and ascertain their validity for being used as substitutes for each other. Laser microdissection (LMD) facilitates identification of metabolites in specific tissues, and thus it can aid in exploration of metabolic pathways in target tissues. Objective To compare tissue‐specific metabolites and protodioscin content of Asparagus cochinchinensis (Lour.) Merr. and Asparagus racemosus Willd. used in China and India. Methods Metabolite analysis of laser‐dissected tissues was carried out using UHPLC–QTOF/MS and LC–MS/MS. The protodioscin contents were determined and the method was validated as per the International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use guidelines. Results Metabolite analysis reveals that the velamen tissue, among other tissues such as cortex, vascular bundles and pith, contained maximum components, specifically those belonging to the steroidal saponin class. Although the metabolite profiles were similar, the content of protodioscin was found to be higher in Chinese than Indian species. Conclusion The study provided a suitable methodology for metabolite profiling and protodioscin content determination of Asparagus by use of LMD, UHPLC–QTOF/MS and LC–MS/MS. The similarities in metabolite profiles indicate that Asparagus species from India and China can serve as substitute for each other in various therapeutic and pharmaceutical applications. Copyright © 2014 John Wiley & Sons, Ltd.